Pengaruh Kepemimpinan Kepala Sekolah Dan Motivasi Kerja Terhadap Kinerja Guru SMP di Kecamatan Luak - Zuraida; Iswantir M (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the effect of principal leadership and teacher work motivation on teacher performance at junior high schools in Luak District, Lima Puluh Kota Regency. A quantitative approach with an associative method was employed. The study involved 51 teachers selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 27. Prior to hypothesis testing, classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity tests were conducted. The results show that principal leadership has a significant effect on teacher performance with a contribution of 57.9%. Teacher work motivation also has a significant effect, although with a lower contribution of 14.6%. Simultaneously, both variables significantly influence teacher performance with a combined contribution of 68.3%. It can be concluded that teacher performance is influenced by the combination of principal leadership and teacher work motivation. Effective leadership and high work motivation play important roles in improving teacher performance in schools.